(untitled) (Rudarsko-geološko-naftni zbornik, 2021)
Rock drilling is the process of penetrating and crushing rocks, which is characterized by the low rate of penetration (ROP) and drilling rate because of the amount of cuttings that remain in the drilling environment and the thermal stresses generated at the bit-rock interface. Any improvement in ROP and drilling rate can be of great technical and economic value for drilling projects. ROP can be improved through the proper use of cooling-lubricating fluids during drilling. ROP is a key indicator of drilling performance and the ability to predict this rate can be very useful for mining projects. ROP prediction can also be used to estimate the total cost of a drilling operation. ROP depends on a variety of parameters, which, when available, can be used to estimate ROP. To reach a better understanding of the parameters affecting ROP and how it can be optimized, in this study, the results of 492 laboratory drilling tests were analyzed by linear and nonlinear multivariate regression in SPSS to build a number of models for ROP prediction. These tests were conducted on seven soft and hard rock samples while using six fluids as the cooling-lubricating agent. The tests were performed with a laboratory-scale drilling rig on cubic specimens at several different rotation speeds and thrust forces. The results showed that the drilling achieved significantly higher ROP in the presence of the cooling-lubricating agent. After reviewing the results, several models that were able to produce ROP predictions with the lowest average estimation error were picked as suitable choices for predicting ROP in the presence of cooling-lubricating fluids. The results of statistical tests of these models showed with over 90% confidence that they can produce highly accurate ROP estimates based on mechanical properties of the rock, physical characteristics of the cooling-lubricating fluid, and operating parameters of the drilling rig.